1992
DOI: 10.1128/iai.60.8.3262-3267.1992
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific growth of Nocardia asteroides in the murine brain

Abstract: The growth of Nocardia asteroides GUH-2 and two mutants (NG-49 and I-38-syn) in regions of the brains of BALB/c mice was determined by microdissection and viable counting. GUH-2 grew throughout the murine brain but at different growth rates that depended on the specific location. The rate of increase in total CFU per brain during GUH-2 infection was unaffected by the inoculum size; however, in five of eight brain regions, an alteration in the inoculum size resulted in altered nocardial growth rates. Mutant NG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Khobata & Beaman, 1991 reported that a sublethal injection of Nocardia cyriacigeorgica GUH-2 can induce a syndrome in mice which shares clinical and pathological similarities with PD. These results were confirmed in other studies (Khobata & Beaman, 1991;Ogata & Beaman, 1992).…”
Section: Introductionsupporting
confidence: 89%
“…Khobata & Beaman, 1991 reported that a sublethal injection of Nocardia cyriacigeorgica GUH-2 can induce a syndrome in mice which shares clinical and pathological similarities with PD. These results were confirmed in other studies (Khobata & Beaman, 1991;Ogata & Beaman, 1992).…”
Section: Introductionsupporting
confidence: 89%
“…Also, N. asteroides GUH-2 metabolizes tyrosine to produce an iron-binding compound (19). Since glutamate, acid phosphatase, and tyrosine are important components in specific regions of the brain (20,21), the ability of GUH-2 to preferentially metabolize these compounds may be significant for its survival and preferential growth within neurons in regions such as the pons, substantia nigra, red nucleus, thalamus, and hypothalamus (18).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate visualization of the localized growth of the nocardiae in the brain, a lethal dose of 106 CFU per mouse (0.1 ml of the bacterial suspension) was injected into the tail vein. It was shown that, at this dose, approximately 800 to 1,000 CFU became localized within the brain 3 h after injection (16)(17)(18). Preparation of the infected brain for electron microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…277 indicate that the ability to induce neurodegeneration could be widely distributed in the Nocardia 278 genus. 279 280 Dopaminergic neuron neurodegeneration 281 The N. cyriacigeorgica GUH-2 strain can invade the neuronal central system and cause 282 dopaminergic neurodegeneration in mice (Ogata & Beaman, 1992). Here we demonstrate that 283 this property induced by N. cyriacigeorgica can be obtained using a rapid test with the C. 284 elegans BY250 vtIs7 [Pdat-1:GFP]) line.…”
mentioning
confidence: 99%